Evaluation of differences in health-related quality of life in patients receiving conventional versus newer anti-epileptic drugs - Goswami, Kavisha S.; Rana, Devang A.; Shah, Shalin; Malhotra, Supriya D. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Epilepsy is associated with stigma and bad health-related quality of life (HR-QOL) due to this, and side effects of the drug therapy. Newer anti-epileptics are claimed to be better than the conventional. We evaluated this based on comparison of HR-QOL in patients taking the respective therapy. Methods: An observational, cross-sectional, single point study involved 127 consenting patients from Neurology OPD at V.S. General Hospital. Quality of life in epilepsy-10 (QOLIE-10) questionnaire was used to measure HR-QOL in patients. SPSS software and Graphpad prism were used to analyze the variables. Results: Patients of 20-30 age group were commonly affected (37.80%) with a male predominance (56.69%). 41.73% were unemployed. The difference in HR-QOL between patients and controls in all three domains (epilepsy effects, mental effects, role function domains) of QOLIE-10 was significant (p=0.0002), indicating better HR-QOL in controls. The worst HR-QOL scores were found in Epilepsy effects domain. Metabolic adverse effects (38.58%) were the common ADRs. Sodium valproate was the most effective in controlling seizures (last seizure episode: 15 months). HR-QOL correlation between patients receiving monotherapy and polytherapy was significant (p=0.026) with monotherapy rendering a better HR-QOL. Comparison of HR-QOL between patients taking the conventional and the newer drugs was not significant (p=0.1768). Conclusions: Our study nullifies the claims that newer drugs are better than the conventional since no such benefit was seen in HR-QOL as well as ADRs. Our findings ruled out the belief that cases of epilepsy are better controlled with polytherapy.